2021
DOI: 10.3390/su13084396
|View full text |Cite
|
Sign up to set email alerts
|

Compaction Procedures and Associated Environmental Impacts Analysis for Application of Steel Slag in Road Base Layer

Abstract: In recent years, recycling steel slag is receiving growing interest in the road base layer construction field due to its role in alleviating land occupation and resource shortages. However, the mixture compaction and its environmental impact on practical construction sites remain unclear, which may hinder the application of steel slags in road layers. This study investigates the pavement construction of the ‘Baotou-Maoming’ motorway, located in Inner Mongolia, China, analyzing the compaction procedures and ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Gao, et al [38] discussed the compaction process of SS base and andesite (a natural aggregate) base. The 98% compaction degree in the standard is used as the evaluation index [99].…”
Section: Environmental Impactsmentioning
confidence: 99%
“…Gao, et al [38] discussed the compaction process of SS base and andesite (a natural aggregate) base. The 98% compaction degree in the standard is used as the evaluation index [99].…”
Section: Environmental Impactsmentioning
confidence: 99%
“…At the same time, this makes the whole concrete frame denser to a certain extent and improves its mechanical properties after mixing. Gao et al [ 17 ], based on the characteristic that the appearance texture and density of steel slag is denser than natural crushed stone, found that the shrinkage and the mechanical performances became stronger after mixing steel slag into concrete. Pasetto et al [ 18 ] optimized the ratio of steel slag and crushed stone aggregate to modify the mechanical property and durability of the mixture.…”
Section: Introductionmentioning
confidence: 99%
“…Steel slag contains iron, CaO, and MgO, which can be utilized as sintering materials [11]. Additionally, steel slag has been demonstrated to be environmentally friendly and possesses cementing properties when used as a subgrade material [12,13]. Steel slag can also be applied to prepare microcrystalline glass.…”
Section: Introductionmentioning
confidence: 99%